Multi-nozzle abrasive water jet for oil and gas platforms decommissioning: A review - Alaloul, W.S. (Horizon Research Publishing, 2021)
Decommissioning offshore platforms present unique safety and health challenges to the oil and gas industry. In the Malaysian waters, there are over 300 fixed jacket platforms, and most of them exceeded the design service life of 25 to 30 years. One of the key challenges that determine the method of removal of aged jacket platforms is subsea cutting techniques. As underwater cutting is a challenging and expensive task, it is very much essential to develop cost-effective cutting techniques for decommissioning fixed jacket platforms. Thus, the objective of this paper is to present the state of art on Abrasive Water Jet (AWJ) cutting techniques by identifying the most significant parameters affecting the performance output measures for decommissioning of Jacket platforms applications. As the cutting process is very complex and times consuming tasks, the paper identifies research gaps and recommends new research areas in Multi Nozzles Abrasive Water Jet (MN-AWJ) for decommissioning applications. Many parameters are affecting the performance of AWJ that is why an in-depth critical review was adopted in this manuscript to determine the most significant parameters that need to be considered in the optimization of AWJ performance. Â© 2021 by authors, all rights reserved.